Improved analytical model for circumferential behavior of jointed shield tunnels considering the longitudinal differential settlement. (January 2015) - Gong, Wenping; Juang, C. Hsein; Huang, Hongwei; Zhang, Jie; Luo, Zhe
Abstract : Graphical abstract: Highlights: An improved analytical model for analysis and design of shield tunnels is presented. Effect of the longitudinal differential settlement on tunnel behavior is studied. Both shearing and flattening effects are incorporated in the proposed method. The variation of tunnel behavior along the longitudinal direction is investigated. Factors affecting the tunnel circumferential behavior are studied. Abstract: Differential settlements of the shield tunnel along the longitudinal direction can significantly affect the circumferential behavior of segmental lining, degrading both the structure safety and serviceability. In this paper, the authors introduce both the shearing effect and flattening effect on the tunnel cross section, which was caused by the longitudinal differential settlement, into an existing analytical model of jointed shield tunnels. An example is then presented to illustrate the variation of the circumferential behavior of segmental lining, including both the structure safety and serviceability, along the longitudinal position. Finally, a series of parametric studies are performed to investigate how factors such as tunnel longitudinal settlement, property of surrounding ground, and the design parameters of segmental lining affect the circumferential behavior of the segmental lining.